Alteration of BDNF in the medial prefrontal cortex and the ventral hippocampus impairs extinction of avoidance. (December 2018) - Rosas-Vidal, Luis; Lozada-Miranda, Valeria; Cantres-Rosario, Yisel; Vega-Medina, Alexis; Melendez, Loyda; Quirk, Gregory
Abstract Brain-derived neurotrophic factor (BDNF) is critical for establishing activity-related neural plasticity. There is increasing interest in the mechanisms of active avoidance and its extinction, but little is known about the role of BDNF in these processes. Using the platform-mediated avoidance task combined with local infusions of an antibody against BDNF, we show that blocking BDNF in either prelimbic (PL) or infralimbic (IL) medial prefrontal cortex during extinction training impairs subsequent recall of extinction of avoidance, differing from extinction of conditioned freezing. By combining retrograde tracers with BDNF immunohistochemistry, we show that extinction of avoidance increases BDNF expression in ventral hippocampal (vHPC) neurons, but not amygdala neurons, projecting to PL and IL. Using the CRISPR/Cas9 system, we further show that reducing BDNF production in vHPC neurons impairs recall of avoidance extinction. Thus, the vHPC may mediate behavioral flexibility in avoidance by driving extinction-related plasticity via BDNFergic projections to both PL and IL. These findings add to the growing body of knowledge implicating the hippocampal-prefrontal pathway in anxiety-related disorders and extinction-based therapies.